Tax On Industrial B3 Waste As An Environmental Control Instrument In Bekasi District - Saragi, Daniel Edgar Hirasma; Firmansyah, Amrie (WIM Solusi Prima, 2024)
Industry in an area can cause environmental quality degradation due to hazardous and toxic (B3) waste generated and polluting the environment. To maintain environmental sustainability in the future, it is necessary to establish a policy to control B3 waste disposal activities. Tax, as one of the regular end instruments, is a tool that the government can use to control waste disposal and is a source of earmarking state revenue. This study analyzes the scheme, benefits, and challenges of taxing industrial hazardous waste disposal. Thus, this policy can be a control tool and source of revenue to overcome negative environmental impacts due to company activities. This research applies a qualitative method with literature study data collection techniques. The literature study analyzed documents related to the research topic, such as letters, photo archives, meeting minutes, journals, diaries, etc. The research concludes that taxation of B3 waste disposal can be applied by official assessment by the Bekasi Regency Regional Government by establishing a special location where the tax subject disposes of its waste and determining the amount of tax payable. The rate used is advalorem, which refers to the capacity of the waste disposed by the company. Administrative aspects, legal certainty, and supervision are critical in implementing this policy. The policy can be implemented if the government has provided adequate infrastructure, resources, monitoring, and law enforcement mechanisms. This research is expected to prepare public policies related to economic and environmental management by the Indonesian government at the regional government level.